Biofilm targeting with chitosan-based nanohydrogel containing Quercus infectoria G. Olivier extract against Streptococcus mutans: new formulations of a traditional natural product - Yasin Karimi; Marzieh Rashidipour; Maryam Iranzadasl; Mohammad Hossein Ahmadi; Mostafa Moradi Sarabi; Fatemeh Farzaneh (BMC, 2024)
Abstract Background Biofilm formation has a crucial role in the cariogenic virulence of Streptococcus mutans, which leads to resistance to common antibacterials. The antimicrobial resistance crisis has led to increased research about traditional natural products. Purpose Quercus infectoria extract (QI extract) and nano hydrogels containing QI extract (QI-NH) and tannic acid (TA-NH) were evaluated against this pathogen. Methods QI extract was analyzed by HPLC and the physiological characteristics of nanohydrogels were assessed by SEM, FTIR, zeta potential, DLS and determination of release kinetics and encapsulation efficiency. Determination of MIC and MBC of the material and their anti-biofilm effect was done by the microtiter method and on the extracted tooth surface. The properties of extracts and nano hydrogels in the expression of genes codifying glucosyltransferases (gtfB, gtfC and gtfD) and glucan binding protein B (gbpB) were quantified. Their toxicity was tested by the MTT method against the KB cell line. Results According to HPLC, 55.18% of QI extract contained TA. The encapsulation efficiency of QI-NH and TA-NH was equal to 60% and 80%, respectively. SEM and FTIR exhibited that QI extract and TA were successfully entrapped in the networks resulting from the chemical bonding of chitosan and TPP. The average size of QI-NH and TA-NH was 70.45 and 58.43 nm, and their zeta potential was 6.17 ± 2.58 and 0.25 ± 0.03 mv, respectively. PDI < 0.3 of nano hydrogels indicated the favorable polydispersity of nanohydrogels. MIC of QI extract, QI-NH and TA-NH were 937.5, 30 and 10 µg/ml, respectively. Also their MBIC50 was 35.1, 2.1 and 0.95 µg/ml, respectively, and the extracts and nano hydrogels restrained the biofilm maturation on enamel. The pivotal genes of S. mutans in biofilm formation were significantly less expressed by treatment with QI-NH and TA-NH than others. Based on the MTT test, QI-NH had less acute toxicity than QI extract and TA-NH. IC50 of QI-NH was calculated as 775.4 µg/ml, while it was equal to 3.12 µg/ml for chlorhexidine as a common antibacterial agent. Conclusion QI-NH, a new formulation derived from traditional anti-caries, can be a safe and efficient option to combat dental biofilm.